2005
DOI: 10.2105/ajph.2004.040063
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of Maternal Deaths on Death Certificates and the Magnitude of the Problem of Maternal Mortality

Abstract: The number of maternal deaths is substantially underestimated when death certificates alone are used to identify deaths, and it is unlikely that the Healthy People 2010 objective of reducing the maternal mortality rate to no more than 3.3 deaths per 100000 live births by 2010 can be achieved. Increasing numbers of births to older women and multiple-gestation pregnancies are likely to complicate efforts to reduce maternal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 15 publications
2
75
0
7
Order By: Relevance
“…Several reports have shown that vital statistics data alone under-report maternal deaths as much as 30 to 60% compared to enhanced surveillance. [18][19][20][21] Furthermore, our institution is a regional perinatal center, which accepts referral of women at high risk of morbidity and death.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that vital statistics data alone under-report maternal deaths as much as 30 to 60% compared to enhanced surveillance. [18][19][20][21] Furthermore, our institution is a regional perinatal center, which accepts referral of women at high risk of morbidity and death.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Europe suggest that underreporting of perinatal suicide on death certificates is in the range of 26% to 56%, 10,11 given that the presence of a child, or perhaps a birth, does not always emerge during the investigation of a death. 1,4,9,12,13 Despite high-profile media attention and calls to increase knowledge, with the goal of encouraging policy change, little is known about the true extent of the problem in Canada or the steps that can be taken to prevent it. 14,15 Greater knowledge about the suicide rate during pregnancy and the postpartum period, as well as the characteristics and patterns of health service use of women who die by suicide, is critical to inform suicide prevention strategies for perinatal women, and ultimately to reduce maternal mortality.…”
mentioning
confidence: 99%
“…Maryland DHMH also identifies pregnancy-associated deaths from other sources, including linkage of death records with birth and fetal death records and review of medical examiner records. 5,7 The availability of comprehensive data collected from multiple sources provided the opportunity to study the effectiveness of check boxes on death certificates in identifying pregnancy-associated deaths. The few previous studies that have assessed the effectiveness of pregnancy check boxes did not use comprehensive, enhanced surveillance to identify all pregnancy-associated deaths, including deaths due to nonmedical causes, such as accidents, homicide, and suicide.…”
mentioning
confidence: 99%